1978
DOI: 10.1007/bf01126546
|View full text |Cite
|
Sign up to set email alerts
|

Flie�verhalten von Schmelzk�sen unter der Wirkung verschiedener Phosphate

Abstract: Processed cheese was manufactured with different types of phosphates (P1 monophosphate to P4 tetrapolyphosphate) and by various techniques. The limiting viscosity numbers of sodium casein and the casein of processed cheese were determined and the axial ratio calculated. The axial ratio of processed cheese protein was a/b=20,0 and that of sodium casein 10,0 resp. We deduce that the apparent increase of the axial ratio is caused by the depolymerization of casein caused by emulsifying salts. The flow curves of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Processed cheese in liquid state behaves as a pseudoplastic liquid and follows the power law (Kirchmeier et al, 1978;Dimitreli and Thomareis, 2004). Figure 4 shows the flow curves of sample 4 made with different emulsifying salts.…”
Section: Flow Behavior Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Processed cheese in liquid state behaves as a pseudoplastic liquid and follows the power law (Kirchmeier et al, 1978;Dimitreli and Thomareis, 2004). Figure 4 shows the flow curves of sample 4 made with different emulsifying salts.…”
Section: Flow Behavior Indexmentioning
confidence: 99%
“…Schulz and Hetzel (1960) and Meyer (1973) have reported the Brabender Plastograph's consistency of processed cheeses made with different types of emulsifying salts. Kirchmeier et al (1978) studied the effect of phosphates (monophosphate to tetrapolyphosphate) on processed cheese apparent viscosity by the use of a coaxial-cylinder viscometer. Furthermore, the effects of trisodium citrate and phosphates on water-soluble nitrogen and relative casein content of processed cheeses were evaluated by Thomas et al (1980).…”
Section: Introductionmentioning
confidence: 99%
“…60 Differences in depolymerization of casein and changes in the flow properties of processed cheese are related to differences in calcium complexation between mono-and tetrapolyphosphates. 61 Melting rate, ultrafiltratable calcium concentration and textural properties (stress/relaxation, hardness, gumminess and elasticity) of processed cheese are affected more by varying the condensed phosphate than the polyphosphate concentrations. 62 Sharpf 63 suggested that the emulsifying effect of chain phosphates is associated with their interaction with paracasein in such a way that phosphate anions form bridges between protein molecules.…”
Section: Of Ofmentioning
confidence: 99%